2009
DOI: 10.1016/s1658-3876(09)50038-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of pediatric patients with stage IV Hodgkin lymphoma

Abstract: Stage IV disease is associated with poor risk features and confers a worse outcome than stage I-III disease. Achievement of complete remission with CT is an important prognostic feature. Slow responders may require novel and/or aggressive therapy to achieve complete remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We also observed that bulky disease significantly affects outcome; this result was also shown in other published studies [28] [30]; this may be related by the relatively prolonged period interval between the onset of symptoms, diagnosis, and treatment outset.…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that bulky disease significantly affects outcome; this result was also shown in other published studies [28] [30]; this may be related by the relatively prolonged period interval between the onset of symptoms, diagnosis, and treatment outset.…”
Section: Discussionsupporting
confidence: 89%
“…However, low-risk patients with late relapse and limited stage may be retrieved with standard dose chemotherapy (SDCT) and RT. The most common prognostic factors are chemosensitivity to initial salvage therapy [110], primary progressive disease [111, 112], time to relapse [113], and extranodal disease [114]. As with adult patients, pediatric patients also show poor prognosis, associated with time from diagnosis to first relapse of <1 year [115].…”
Section: Treatmentmentioning
confidence: 99%
“…A study by Belgaumi et al reported less than 80% of patients had HL, 94% were diagnosed with early stage, and 96% were late stage patients [ 29 ]. For patients of early- and advanced-stage HL, a variety of prognostic variables were identified: bulky disease, ESR, LDH, hemoglobin, and the presence of B-symptoms, with age being the most important one [ 30 ].…”
Section: Discussionmentioning
confidence: 99%